The behaviour of fluorine, chlorine, and sulphur in the magma of Merapi Vulcano Central Java – Indonesia - E. Kadarsetia; J. Hirabayashi; T. Ohba; K. Nogami (Badan Geologi, 2010)
ABSTRACTMerapi volcano, located at Central Java - Indonesia, is one of the world’s most active volcano. In order to gain better understanding on volcanism and magmatism of this calc-alkaline volcano, various researches have been carried out. Some valuable information concerning volcanism of Merapi volcano can be indirectly obtained through the investigation of fluorine, chlorine and sulphur behavior in the magma. To accomplish this study, sixteen rock samples have been taken from the summit. Petrographic and chemical analysis of the rocks had been carried out. Major elements composition, analyzed by X-ray fluoresence method, shown that during the last 100 years chemical composition of magma have not been significantly changed, about 55 wt% of SiO2. Chemical composition of individual minerals, determined by EPMA, suggested a constant composition the magma. Bulk compositions of fluorine and chlorine were determined by wet analytical methods, Ion-selective Electrode “by Trymethylsilylating distillation” method and spectrophotometer determination by Mercury Thiocyanate method respectively. On the other hand, sulphur was determined by a fluorescence instrumental method. The concentration of fluorine, chlorine and sulphur are 210 - 390 ppm, 60 - 540 ppm (water insoluble) and 17 - 82 ppm respectively. The relationship between Cl with Si02 and CaO could be observed. F in agreement with CaO, and in general correlate with the volume of hydrous minerals. Most of F/Cl atomic ratio of Merapi rocks >1, and decrease with increasing Si02, or F is more reactive than Cl to the magma, especially in the earlier stage of crystallization. The equal size of fluorine and hydroxyl ions permits fluorine to substitute easily for OH- in hydrous minerals or melt, Cl may be expelled during crystallization when in the fluorine present. In more residual magma the larger ionic radius of chlorine and its renown ability to form complex molecules should lead to greater concentration of chlorine than fluorine; these facts as well as the water solubility of chlorine compounds, that have been advanced as an explanation for the high Cl/F ratio obtained in volcanic gases. Sulphur has parallel correlation with FeO. It is shown that sulphur was more partioned into Fe rich magma, whereas Fe-S mineral is more likely. Therefore, the low sulphur content of Merapi lava might be as the characteristics of island arc volcanism.Keywords: Composition magma of Merapi, chlorine, fluorine, sulphur